Focussed beam reflectance measurement (FBRM) monitoring of particle size and morphology in suspension cultures of Morinda citrifolia and Centaurea calcitrapa - Jeffers, Paul (2014)
Laser light scattering technology, as applied in the Lasentec focussed beam reflectance measurement (FBRM) system, was used to characterise two morphologically dissimilar plant cell suspension cultures, Morinda citrifolia and Centaurea calcitrapa. Shake-flask suspensions were analysed in terms of biomass concentration and aggregate size/shape over the course of typical batch growth cycles. For the heavily aggregated C. calcitrapa, biomass levels [from 10-160 g fresh weight (fw) l-1)] were linearly correlated with FBRM counts. For M. citrifolia, which grows in unbranched chains of 2-10 elongated cells, linear correlation of biomass concentration with FBRM counts was applicable in the range 0-100 g fw l-1; at higher levels (100-300 g fw l-1), biomass was non-linearly correlated with FBRM counts and length-weighted average FBRM chord length. For both cell systems, particle morphology (size/shape) was quantified using semi-automated digital image analysis. The average aggregate equivalent diameter (C. calcitrapa) and average chain length (M. citrifolia), determined using image analysis, closely tracked the FBRM average chord length. The data clearly demonstrate the potential for applying the FBRM technique for rapid characterisation of plant cell suspension cultures.